Spatio-temporal variability in drifting Fish Aggregating Device (dFAD) beaching events in the Seychelles Archipelago. (25th May 2022) - MacMillan, Isla; Attrill, Martin J; Imzilen, Taha; Lett, Christophe; Walmsley, Simon; Chu, Clarus; Kaplan, David M
Abstract: Purse-seine fisheries use drifting Fish Aggregating Devices (dFADs), human-made floating objects, to facilitate the capture of tropical tunas. Currently, the majority of dFADs are constructed primarily of highly durable non-biodegradable materials and there is no legal obligation to recover dFADs after deployment, leading to beaching events and potentially negative environmental impacts. We assessed beachings as a function of intra- and inter-annual trends, water depth, distance from land, seasonality, and benthic habitat within the local context of the Seychelles Archipelago using trajectories of dFADs deployed by French purse seiners over 2008–2020. Overall, 3842 beaching events associated with 2371 distinct dFAD tracking buoys were identified. Beachings occurred most frequently during the winter monsoon (December–March). Due to the shallow Mahé Plateau, beachings occurred in both nearshore (≤ 5 km from land) and offshore (> 5 km) regions, predominantly in estimated depths less than 60 m. Despite representing < 20% of overall mapped habitat, the benthic habitat "Coral/Algae" had the highest beaching rate (35.3% of beachings), and therefore, beachings pose a significant concern for conservation. Our results provide a detailed view of the spatio-temporal pattern of beachings in the Seychelles, supporting the development of mitigation and prevention methods to reduce marine debris and perturbations to the marine environment.